Enhancement in physicochemical parameters and microbial populations of mushrooms as influenced by nano-coating treatments - Rokayya Sami (Nature Portfolio, 2021)
Abstract White button mushrooms are greatly high perishable and can deteriorate within a few days after harvesting due to physicomechanical damage, respiration, microbial growth of the delicate epidermal structure. For that reason, the present research work was applied to evaluate the effect of chitosan combination with nano-coating treatments on physicochemical parameters and microbial populations on button mushrooms at chilling storage. Nano coating with the addition of nisin 1% (CHSSN/M) established the minimum value for weight loss 12.18%, maintained firmness 11.55 N, and color index profile. Moreover, O2% rate of (CHSSN/M) mushrooms was the lowest at 1.78%; while the highest rate was reported for CO2 24.88% compared to the untreated samples (Control/M) on day 12. Both pH and total soluble solid concentrations increased during storage. Results reported that the (CHSS/M) mushroom significantly (P < 0.05) reduced polyphenol oxidase activity (24.31 U mg−1 Protein) compared with (Control/M) mushrooms that increased faster than the treated samples. (CHSSN/M) treatment was the most efficient in the reduction of yeast and mold, aerobic plate microorganisms (5.27–5.10 log CFU/g), respectively. The results established that nano-coating film might delay the aging degree and accompany by marked prolongation of postharvest mushroom freshness.